How can ILCA help enhance animal productivity in Africa - Scholtens, R. (Sokoine University of Agriculture, 1985)
Because of Africa's dependence on livestock two CGIAR centers committed to animal agriculture have been established - ILCA and ILRAD. ILCA conducts research on livestock production, systems, animal nutrition, livestock diseases, trypanotolerant animal production, forage agronomy, land-use ecology, dairy technology, animal traction, livestock economics and policy and other facets of animal agriculture in all the agroclimatic zones of Africa. ILCA is an established scientific institution responsible for the collection, maintainance, use and distribution of information on African livestock, research on ways to identify and reduce the constraints to livestock production, and the training in the various aspects of animal agriculture. The paper looks at the number and distribution of livestock in Africa, diverse uses of livestock, and livestock Development strategies discussing the major problem areas to consider that will lead to increased livestock productivity. These areas are production constraints, ecological constraints, and population constraints. Those countries that are highly dependent on livestock should be ILCA's prime clients and partners in the enhancement of livestock production.